INFLUENCE OF THE PSYCHOLOGICAL ENVIRONMENT IN THE FAMILY ON THE DEVELOPMENT OF THE CHILD - Rimbayeva Ozoda Bazarbayevna (Western European Studies, 2024)
Since a child is born and raised in the family, the environment in the family shows its significant influence on its development. Depending on the extent to which it is physically and mentally developed, we can evaluate the psychological environment in the family
Keywords: psychological; family; pedagogical neglect